Enlargement of Phimotic Capsulorhexis Using Plasma Energy: A Case Series - V. Kumar (Oftalʹmologiâ, 2021)
Purpose: to evaluate the effectiveness and safety of the plasma ablation technique of Fugo blade system to enlarge phimotic capsulotomies in the management of anterior capsule contraction syndrome.Patients and methods. Results of the enlargement of phimotic capsulotomies using the plasma ablation technique in 17 patients with anterior capsule contraction syndrome (10 men and 7 women, 18 eyes; average age — 73.8 ± 9.6 years) were retrospectively analyzed. Surgically, after pupil dilation, the anterior chamber was irrigated with a viscoelastic device (1.4 % solution of hyaluronic acid), and the tip of the Fugo blade was inserted through a 2.0–2.2 mm wide corneal incision. After slightly touching the anterior capsule, the apparatus was activated, and its tip was moved in a concentric manner, excising the required size of the fibrosed anterior capsule in a resistance-free fashion. Finally, the viscoelastic material was aspirated, and the incisions were hydrated.Results. Phimotic capsulotomies were enlarged in all cases. Except for three cases where the bimanual technique was required to ablate the anterior capsule, all other cases were managed single-handedly. The use of cohesive viscoelastic device (1.4 % solution of hyaluronic acid) made it possible to perform this procedure with minimum trauma and under visual control. No serious complications were encountered during surgery or in the early postoperative period. Patients were discharged 1–2 days after surgery. Corneal edema, which was observed in six eyes, resolved within 3–4 days. Visual acuity improved in all cases, except for 2 patients with complete glaucomatous optic atrophy. IOP remained under control in all cases. No negative effect on the hypotensive results of previous glaucoma surgeries was observed.Conclusion. The plasma-generating Fugo blade system is an effective and safe tool to enlarge phimotic capsulorhexis in a resistance-free fashion. It is easy to use, mastering of new surgical skills is not required, surgical trauma is minimal, the surgical time is reduced, and the patient’s rehabilitation period is significantly shortened.